A vacuum evaporation perovskite-organic hybrid laminated white light LED and a preparation method thereof

CN122995414APending Publication Date: 2026-10-27河南省科学院半导体研究所
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611216116.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-12
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

本发明通过真空蒸镀代替溶液旋涂法获得高质量的红光钙钛矿薄膜,同时在红光钙钛矿薄膜与电荷产生层之间设置同类型CsPbCl3钙钛矿量子点修饰层实现表面钝化和电子注入改善,再与蓝光有机单元叠层,在宽电压范围内获得了高效稳定的白光发射,以此解决现有技术中钙钛矿发光单元电子注入效率低、界面缺陷密度高、光谱稳定性差以及难以实现高效白光发射的技术问题

Benefits of technology

[0027]1. 本发明采用多源真空蒸镀法制备红光准二维钙钛矿发光层,薄膜致密均匀、无针孔、重复性好,解决了溶液法薄膜质量差和层间互溶的问题;同时与溶液旋涂法制备量子点修饰层的工艺路线良好兼容、简单,适合大面积量产。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122995414A_ABST
    Figure CN122995414A_ABST
Patent Text Reader

Abstract

The application belongs to the technical field of light emitting diodes, and discloses a vacuum evaporation perovskite-organic hybrid laminated white light LED and a preparation method thereof. The white light LED comprises an anode, a composite hole transport layer, a red light quasi-two-dimensional perovskite light emitting layer, a perovskite quantum dot modification layer, a charge generation layer, a blue light organic light emitting layer, an electron transport layer and a cathode which are sequentially laminated. The red light quasi-two-dimensional perovskite light emitting layer is formed by multi-source vacuum evaporation. The high-quality red light quasi-two-dimensional perovskite light emitting layer is obtained by the vacuum evaporation method, and the same type of CsPbCl3 perovskite quantum dot modification layer is arranged to realize the dual functions of surface passivation and electron injection improvement. Then, the blue light organic light emitting unit is laminated to obtain high-efficiency and stable white light emission in a wide voltage range of 8-13 V, the CIE color coordinates are (0.323, 0.316), the maximum brightness is 5327 cd / m 2 , and the maximum external quantum efficiency reaches 17.1%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of light-emitting diode technology, specifically relating to a vacuum-deposited perovskite-organic hybrid stacked white LED and its preparation method. Background Technology

[0002] Amidst the rapid development of solid-state lighting and display technologies, white light-emitting diodes (WLEDs) have become the mainstream technology in the lighting and display fields due to their advantages such as high efficiency, energy saving, fast response speed, and small size. In recent years, perovskite materials, with their excellent optoelectronic properties such as high fluorescence quantum yield, tunable wavelength, and high color purity, have become strong competitors for next-generation display and lighting technologies. Currently, the external quantum efficiency of red, green, and near-infrared perovskite light-emitting devices has exceeded 25%, but the development of perovskite-based white light devices still faces significant challenges.

[0003] Existing perovskite white light devices are mainly divided into all-perovskite WLEDs and perovskite / organic hybrid WLEDs. All-perovskite WLEDs are limited by the low efficiency of blue perovskite devices and the difficulty in precisely controlling heterogeneous components, resulting in generally low device efficiency (the highest EQE is only 12.2%). Although perovskite / organic hybrid WLEDs can use a stacked structure to suppress energy transfer, the low electron injection efficiency and high interface defect density of the perovskite light-emitting unit lead to insufficient red light emission intensity and carrier injection imbalance, making it difficult to achieve stable and efficient white light emission over a wide voltage range.

[0004] To address the issues of insufficient electron injection and high interface defect density in perovskite light-emitting units, researchers have attempted to introduce interface modification layers onto the perovskite layer surface. However, traditional interface materials (such as TPBi and MoO3) exhibit poor energy level matching with the perovskite layer and cannot effectively passivate dangling bonds and halogen vacancies on the perovskite surface, resulting in room for improvement in device performance. Furthermore, existing solution-based perovskite film fabrication methods suffer from pinholes, numerous grain boundary defects, interlayer mutual solubility, and poor batch-to-batch reproducibility, making it difficult to meet the industrialization requirements for high uniformity and stability.

[0005] Therefore, how to achieve efficient electron injection and interface defect passivation in perovskite-organic hybrid white LEDs, and obtain stable and efficient white light emission over a wide voltage range, has become a technical problem that urgently needs to be solved in this field. Summary of the Invention

[0006] To address the shortcomings of existing technologies, the present invention aims to provide a vacuum-deposited perovskite-organic hybrid stacked white LED and its fabrication method. This invention obtains a high-quality red-light perovskite thin film by replacing solution spin coating with vacuum deposition. Simultaneously, a CsPbCl3 perovskite quantum dot modification layer of the same type is placed between the red-light perovskite thin film and the charge generation layer to achieve surface passivation and improved electron injection. This layer is then stacked with blue-light organic units, achieving efficient and stable white light emission over a wide voltage range. This solves the technical problems of low electron injection efficiency, high interface defect density, poor spectral stability, and difficulty in achieving efficient white light emission in existing technologies.

[0007] To achieve the above objectives, the present invention adopts the following technical solution:

[0008] The first aspect of this invention provides a vacuum-deposited perovskite-organic hybrid stacked white LED, comprising an anode, a composite hole transport layer, a red quasi-two-dimensional perovskite emitting layer, a perovskite quantum dot modification layer, a charge generation layer, a blue organic emitting layer, an electron transport layer, and a cathode, which are sequentially stacked. The perovskite quantum dot modification layer is disposed between the red quasi-two-dimensional perovskite emitting layer and the charge generation layer. The red quasi-two-dimensional perovskite emitting layer is formed by multi-source vacuum evaporation.

[0009] This invention introduces a perovskite quantum dot modification layer into a perovskite-organic hybrid white LED, positioned between the red-light quasi-two-dimensional perovskite emitting layer and the charge generation layer, simultaneously playing a dual key role: on the one hand, the Cl on the quantum dot surface... - Ions and organic ligands with uncoordinated Pb on the perovskite surface 2+ Coordination and passivation of surface defects reduce nonradiative recombination and improve the radiative recombination efficiency of the red light-emitting unit. On the other hand, quantum dots possess high carrier mobility and an appropriate conduction band energy level (-3.5 eV), forming a good energy level match with the charge generation layer. This significantly improves the electron injection capability of the perovskite light-emitting unit, making the injection of electrons and holes more balanced, thereby increasing the red light emission intensity and its proportion in the stacked device. Optimization of the red perovskite light-emitting unit through the quantum dot modification layer enables the red light-emitting unit to maintain a stable luminous intensity ratio with the blue organic light-emitting unit over a wide voltage range, thus achieving efficient and stable white light emission.

[0010] Furthermore, the perovskite quantum dot modification layer is CsPbCl3 perovskite quantum dots, the average particle size of the CsPbCl3 perovskite quantum dots is 9.9±0.02 nm, and the emission peak is located at 408 nm.

[0011] Furthermore, the red-light quasi-two-dimensional perovskite luminescent layer is formed by multi-source vacuum co-evaporation of lead iodide, phenylethyl ammonium iodide, and cesium bromide.

[0012] Furthermore, the composite hole transport layer comprises a poly(3,4-ethylenedioxythiophene):polystyrene sulfonate layer (PEDOT:PSS layer), a poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine] layer (PTAA layer) and a poly(9-vinylcarbazole) layer (PVK layer) stacked sequentially.

[0013] Furthermore, the charge-generating layer comprises a 1,3,5-tris(1-phenyl-1H-benzimidazol-2-yl)benzene layer (TPBi layer), a MoO3 layer, and an N,N'-diphenyl-N,N'-(1-naphthyl)-1,1'-biphenyl-4,4'-diamine layer (NPB layer) stacked sequentially.

[0014] Furthermore, the blue light-emitting organic light-emitting layer is a 1,3-bis(N-carbazolyl)benzene:bis(4,6-difluorophenylpyridine-C2,N)(pyridinecarboxylate)iridium(III) doped layer (mCP:FIrpic doped layer), wherein the doping concentration of FIrpic is 5-15wt%.

[0015] Furthermore, the thickness of the composite hole transport layer is 55-65 nm, the thickness of the red light quasi-two-dimensional perovskite luminescent layer is 60-65 nm, and the thickness of the perovskite quantum dot modification layer is 3-4 nm.

[0016] Furthermore, the thickness of the charge generation layer is 53-66 nm, the thickness of the blue light organic light-emitting layer is 15-20 nm, and the thickness of the electron transport layer is 30-35 nm.

[0017] A second aspect of this invention provides a method for preparing the above-mentioned vacuum-deposited perovskite-organic hybrid multilayer white LED, comprising the following steps:

[0018] (1) Patterning etching, cleaning and ultraviolet ozone treatment are performed on the ITO glass substrate, and a composite hole transport layer is prepared on the ITO glass substrate by solution spin coating.

[0019] (2) A red light quasi-two-dimensional perovskite luminescent layer was prepared on the composite hole transport layer by a multi-source vacuum co-evaporation method;

[0020] (3) Spin-coating a perovskite quantum dot dispersion onto the red light quasi-two-dimensional perovskite luminescent layer, and then annealing to form a perovskite quantum dot modification layer;

[0021] (4) A charge generation layer is formed by vacuum evaporation on the perovskite quantum dot modified layer;

[0022] (5) A blue organic light-emitting layer is formed by vacuum evaporation on the charge generation layer;

[0023] (6) An electron transport layer and a cathode are sequentially deposited on the blue organic light-emitting layer.

[0024] This preparation method combines vacuum evaporation with solution spin coating: a multi-source vacuum co-evaporation process is used to prepare a red-light quasi-two-dimensional perovskite luminescent layer, effectively avoiding the problems of pinholes, interlayer mutual solubility, and poor batch repeatability associated with solution methods; a solution spin coating method is used to prepare a CsPbCl3 perovskite quantum dot modification layer, which is simple, low-cost, and highly compatible with the vacuum evaporation process. This hybrid process route of vacuum evaporation and solution spin coating ensures both the high quality of the perovskite luminescent layer and precise controllability of the quantum dot modification layer, making it suitable for large-area mass production.

[0025] Further, in the multi-source vacuum co-evaporation method described in step (2), the evaporation rate of lead iodide is 0.3-0.32 Å / s, the evaporation rate of phenylethyl ammonium iodide is 0.15-0.17 Å / s, the evaporation rate of cesium bromide is 0.2-0.22 Å / s, the substrate temperature is 40-45℃, the in-situ annealing temperature is 100-105℃, and the annealing time is 20-25 min; the annealing temperature described in step (3) is 70-75℃, and the time is 5-7 min.

[0026] Compared with the prior art, the beneficial effects of the present invention are as follows:

[0027] 1. This invention uses a multi-source vacuum evaporation method to prepare a red light quasi-two-dimensional perovskite luminescent layer. The film is dense and uniform, free of pinholes, and has good repeatability, solving the problems of poor film quality and interlayer miscibility in solution-based methods. At the same time, it is well compatible with the process route of preparing quantum dot modified layers by solution spin coating, is simple, and is suitable for large-area mass production.

[0028] 2. This application introduces a CsPbCl3 perovskite quantum dot modification layer into a perovskite-organic hybrid stacked white LED, enabling the quantum dots to simultaneously perform the dual functions of surface passivation and improved electron injection. This effectively reduces the non-radiative recombination loss of the red perovskite emitting layer, improves electron injection efficiency, and allows the red emitting unit to maintain a stable luminous intensity ratio with the blue organic emitting unit over a wide voltage range, thus achieving efficient and stable white light emission.

[0029] 3. This invention achieves stable white light emission over a wide voltage range of 8-12 V by stacking red perovskite units optimized with quantum dot modification layers and blue organic units, with CIE color coordinates of (0.323, 0.316), close to the CIE color coordinates of standard white light (0.333, 0.333). The maximum luminance reaches 5327 cd / m², and the maximum external quantum efficiency reaches 17.1%, which is far superior to existing technologies and has clear application prospects. Attached Figure Description

[0030] Figure 1 (a) TEM image and (b) particle size distribution of CsPbCl3 perovskite quantum dots in Example 1;

[0031] Figure 2 The UPS energy level diagram of the CsPbCl3 perovskite quantum dots in Example 1;

[0032] Figure 3 This is a schematic diagram of the structure of the stacked white LED device in Example 3;

[0033] Figure 4 The EL spectra of the single-junction red perovskite LED devices in Example 2 and Comparative Example 1 are shown.

[0034] Figure 5 The voltage-current density-brightness curves of the single-junction red perovskite LED devices in Example 2 and Comparative Example 1 are shown.

[0035] Figure 6 The EL spectrum of the stacked white LED in Example 3;

[0036] Figure 7 The CIE color coordinates of the stacked white LEDs in Example 3;

[0037] Figure 8 The voltage-current density-brightness curves of the stacked white LED in Example 3 are shown.

[0038] Figure 9 The current density-external quantum efficiency curves of the stacked white LED in Example 3 are shown.

[0039] Figure 10 The EL spectrum of the stacked white LED in Comparative Example 2;

[0040] Figure 11 The voltage-current density-brightness curves are for the stacked white LEDs in Comparative Example 2. Detailed Implementation

[0041] The technical solution of the present invention will be further described below with reference to specific embodiments. However, those skilled in the art should understand that the following embodiments are only for illustrating the present invention and should not be regarded as limiting the present invention.

[0042] For experiments not specifically described in the examples, the procedures or conditions should be followed according to the conventional experimental procedures described in the literature in this field. Reagents or instruments whose manufacturers are not specified are all commercially available conventional reagent products.

[0043] Example 1

[0044] The specific steps for preparing CsPbCl3 perovskite quantum dots are as follows:

[0045] S1. Preparation of cesium oleate precursor solution: Add 0.204 g Cs2CO3, 20 mL octadecene (ODE) and 625 μL oleic acid (OA) to a 50 mL three-necked flask; add magnetic stirring, heat to 120 °C, and evacuate for 1 h; introduce N2, raise the temperature to 150 °C, and after Cs2CO3 has completely reacted to form a transparent liquid, cool to room temperature and store under N2 environment for later use.

[0046] S2. Synthesis of CsPbCl3 perovskite quantum dots: 5 mL ODE, 1 mL trioctylphosphine (TOP) and 0.052 g PbCl2 were added to a 25 mL three-necked flask; under continuous vacuum, the mixture was stirred and heated to 150 °C, dried for 1 h and then N2 was introduced; under N2 environment, the temperature was maintained at 150 °C, and 0.5 mL oleylamine (OLA) and 0.5 mL OA were injected, and the mixture was heated until PbCl2 was completely dissolved, forming a pale yellow clear solution; then 0.4 mL of cesium oleate precursor solution preheated to above 100 °C was rapidly injected, and the mixture was placed in an ice-water bath to cool to room temperature within 5 seconds after injection, to obtain a milky white solution.

[0047] S3. Purification: Pour the above milky white solution into a 10 mL centrifuge tube, centrifuge at 12000 rpm for 10 min, and discard the supernatant to obtain a precipitate; redisperse the precipitate in 3 mL of n-hexane, add 2 mL of methyl acetate / n-hexane mixture (2:1, v / v), centrifuge at 12000 rpm for 5 min, and repeat three times; finally, disperse the obtained solid in n-hexane to obtain a clear colloidal CsPbCl3 perovskite quantum dot dispersion with a concentration of approximately 15 mg / mL.

[0048] TEM image of the CsPbCl3 perovskite quantum dot is shown below. Figure 1 As shown in (a), the particle size distribution is as follows: Figure 1 As shown in (b).

[0049] according to Figure 1 (a) It can be seen that the quantum dot has a regular cubic morphology with clearly visible lattice fringes and a lattice spacing of 0.36 nm, corresponding to the (110) crystal plane of the cubic phase CsPbCl3. According to Figure 1 (b) It can be seen that the average particle size of the quantum dot is 9.9 ± 0.02 nm.

[0050] Figure 2 The UPS level diagram of this CsPbCl3 perovskite quantum dot is shown below. Figure 2 It can be seen that the valence band of this CsPbCl3 perovskite quantum dot was measured by UPS to be -6.5 eV, and the conduction band was calculated to be -3.5 eV based on the absorption spectrum band gap.

[0051] Example 2

[0052] This embodiment provides a single-junction red perovskite LED, the structure of which, from bottom to top, includes: an anode, a composite hole transport layer, a red quasi-two-dimensional perovskite light-emitting layer, a perovskite quantum dot modification layer, an electron transport layer, an electron injection layer, and a cathode.

[0053] The anode is ITO glass, and the composite hole transport layer, from bottom to top, includes a 30 nm thick PEDOT:PSS layer, a 15 nm thick PTAA layer, and a 10 nm thick PVK layer. The red quasi-two-dimensional perovskite emitting layer is a 60 nm thick PEA2CsPb2(I) layer prepared by vacuum evaporation. 0.7 Br 0.3 )7. The perovskite quantum dot modification layer is a CsPbCl3 perovskite quantum dot layer with a thickness of 3 nm, the electron transport layer is a TPBi layer with a thickness of 30 nm, the electron injection layer is a LiF layer with a thickness of 1 nm, and the cathode is an Al layer with a thickness of 120 nm.

[0054] This embodiment also provides a method for fabricating the above-mentioned single-junction red perovskite LED, comprising the following steps:

[0055] (1) Preparation of the anode:

[0056] The surface of the glass substrate printed with transparent ITO was patterned; then it was placed in an ultrasonic cleaner and ultrasonically cleaned for 20 minutes each with detergent, deionized water, acetone and isopropanol, and then dried with nitrogen; finally, it was placed in an ultraviolet cleaner for ultraviolet ozone treatment for 20 minutes as the anode.

[0057] (2) Preparation of composite hole transport layer:

[0058] a. A PEDOT:PSS hole transport layer was spin-coated on the surface of an ITO glass substrate after ultraviolet ozone treatment. The spin-coating speed was 4000 rpm and the spin-coating time was 40 s. Then, the substrate was annealed in air at 125°C for 15 min to form a PEDOT:PSS layer with a thickness of 30 nm.

[0059] b. Transfer the ITO glass substrate with the PEDOT:PSS layer to a glove box filled with nitrogen, spin-coat the PTAA hole transport layer, wherein the PTAA is dissolved in chlorobenzene at a concentration of 1.5 mg / mL, the spin-coating speed is 3000 rpm, the spin-coating time is 20s, and then anneal at 120℃ for 10 min to form a PTAA layer with a thickness of 15 nm.

[0060] c. Spin-coating PVK hole transport layer: Dissolve PVK in DMF at a concentration of 1.5 mg / mL, spin-coat it onto the PTAA layer at a spin speed of 3000 rpm for 20 s, and then anneal at 100℃ for 10 min to form a PVK layer with a thickness of 10 nm.

[0061] (3) Preparation of red-light quasi-two-dimensional perovskite emitting layer by vacuum evaporation: The device obtained in step (2) is transferred to the vacuum evaporation chamber and the vacuum degree is evaporated to 1×10 -4 Pa; PbI2, PEAI, and CsBr were co-deposited in three separate evaporation boats, with the evaporation rates of PbI2, PEAI, and CsBr controlled at 0.3 Å / s, PEAI at 0.15 Å / s, and CsBr at 0.2 Å / s, respectively, to a co-deposition thickness of 60 nm. The device temperature was maintained at 40 °C. After deposition, the devices were annealed in situ at 100 °C for 20 min in a vacuum chamber.

[0062] (4) Preparation of perovskite quantum dot modification layer: The CsPbCl3 perovskite quantum dot dispersion synthesized in Example 1 was spin-coated onto the surface of the red light perovskite luminescent layer at a speed of 3000 rpm for 40 s. Then, it was annealed on a hot plate at 70℃ for 5 min to form a CsPbCl3 perovskite quantum dot modification layer with a thickness of about 3 nm.

[0063] (5) Preparation of electron transport layer, electron injection layer and cathode: The device obtained in step (4) is sent back to the evaporation chamber and TPBi with a thickness of 30 nm, LiF with a thickness of 1 nm and Al with a thickness of 120 nm are deposited in sequence.

[0064] Example 3

[0065] This embodiment provides a vacuum-deposited perovskite-organic hybrid stacked white LED, the structure of which is as follows: Figure 3 As shown, from bottom to top, it includes: an anode, a composite hole transport layer, a red light quasi-two-dimensional perovskite light-emitting layer, a perovskite quantum dot modification layer, a charge generation layer, a blue light organic light-emitting layer, an electron transport layer, an electron injection layer, and a cathode.

[0066] The anode is ITO glass, and the composite hole transport layer, from bottom to top, consists of a 30 nm thick PEDOT:PSS layer, a 15 nm thick PTAA layer, and a 10 nm thick PVK layer. The red quasi-two-dimensional perovskite emitting layer is a 60 nm thick PEA2CsPb2(I) layer prepared by vacuum evaporation. 0.7 Br 0.37. The perovskite quantum dot modification layer is a CsPbCl3 perovskite quantum dot layer with a thickness of 3 nm. The charge generation layer from bottom to top includes a TPBi layer with a thickness of 30 nm, a MoO3 layer with a thickness of 6 nm, and an NPB layer with a thickness of 20 nm. The blue light organic light emission layer is an mCP:FIrpic layer with a thickness of 15 nm. The electron transport layer is a TPBi layer with a thickness of 30 nm. The electron injection layer is a LiF layer with a thickness of 1 nm. The cathode is an Al layer with a thickness of 120 nm.

[0067] This embodiment also provides a method for fabricating the above-mentioned device, including the following steps:

[0068] (1) Preparation of anode: The surface of the glass substrate printed with transparent ITO is patterned; then it is placed in an ultrasonic cleaner and ultrasonically cleaned for 20 min each with detergent, deionized water, acetone and isopropanol. Then the surface is dried with nitrogen; it is placed in an ultraviolet cleaner for ultraviolet ozone treatment for 20 min to serve as anode.

[0069] (2) Preparation of composite hole transport layer:

[0070] a. A PEDOT:PSS hole transport layer was spin-coated on the surface of an ITO glass substrate after ultraviolet ozone treatment. The spin-coating speed was 4000 rpm and the spin-coating time was 40 s. Then, the substrate was annealed in air at 125°C for 15 min to form a PEDOT:PSS layer with a thickness of 30 nm.

[0071] b. Transfer the ITO glass substrate with the PEDOT:PSS layer to a glove box filled with nitrogen and spin-coat the PTAA hole transport layer: PTAA is dissolved in chlorobenzene at a concentration of 1.5 mg / mL, the spin-coating speed is 3000 rpm, the spin-coating time is 20 s, and then annealed at 120℃ for 10 min to form a PTAA layer with a thickness of 15 nm.

[0072] c. Spin-coating PVK hole transport layer: Dissolve PVK in DMF at a concentration of 1.5 mg / mL, spin-coat it onto the PTAA layer at a spin speed of 3000 rpm for 20 s, and then anneal at 100℃ for 10 min to form a PVK layer with a thickness of 10 nm.

[0073] (3) Preparation of red-light quasi-two-dimensional perovskite emitting layer by vacuum evaporation: The device obtained in step (2) is transferred to the vacuum evaporation chamber and the vacuum degree is evaporated to 1×10 -4Pa; PbI2, PEAI, and CsBr were co-deposited in three separate evaporation boats, with the evaporation rates of PbI2, PEAI, and CsBr controlled at 0.3 Å / s, PEAI at 0.15 Å / s, and CsBr at 0.2 Å / s, respectively, to a co-deposition thickness of 60 nm. The device temperature was maintained at 40 °C. After deposition, the device was annealed in situ at 100 °C for 20 min in a vacuum chamber.

[0074] (4) Preparation of perovskite quantum dot modification layer: The CsPbCl3 perovskite quantum dot dispersion synthesized in Example 1 was spin-coated onto the surface of the red light perovskite luminescent layer at a speed of 3000 rpm for 40 s. Then, it was annealed on a hot plate at 70℃ for 5 min to form a CsPbCl3 perovskite quantum dot modification layer with a thickness of about 3 nm.

[0075] (5) Preparation of charge generation layer: The device obtained in step (4) is sent back to the evaporation chamber and TPBi with a thickness of 30 nm is deposited in sequence at an evaporation rate of 0.5 Å / s, MoO3 with a thickness of 6 nm is deposited at an evaporation rate of 0.3 Å / s, and NPB with a thickness of 20 nm is deposited at an evaporation rate of 0.5 Å / s.

[0076] (6) Preparation of blue organic light-emitting layer: mCP and Firpic are deposited on the device obtained in step (5) by dual-source co-evaporation method. The evaporation rate of mCP is 1.5 Å / s, the evaporation rate of Firpic is 0.15 Å / s, the doping concentration of Firpic is 10wt%, and the co-deposition thickness is 15 nm.

[0077] (7) Preparation of electron transport layer, electron injection layer and cathode: TPBi with a thickness of 30 nm, LiF with a thickness of 1 nm and Al with a thickness of 120 nm are deposited sequentially on the device obtained in step (6).

[0078] Example 4

[0079] This embodiment provides a vacuum-deposited perovskite-organic hybrid stacked white LED, which, from bottom to top, includes: an anode, a composite hole transport layer, a red quasi-two-dimensional perovskite light-emitting layer, a perovskite quantum dot modification layer, a charge generation layer, a blue organic light-emitting layer, an electron transport layer, an electron injection layer, and a cathode.

[0080] The anode is ITO glass, and the composite hole transport layer, from bottom to top, consists of a 30 nm thick PEDOT:PSS layer, a 20 nm thick PTAA layer, and a 10 nm thick PVK layer. The red quasi-two-dimensional perovskite emitting layer is a 65 nm thick PEA2CsPb2(I) layer prepared by vacuum evaporation. 0.7 Br 0.37. The perovskite quantum dot modification layer is a CsPbCl3 perovskite quantum dot layer with a thickness of 4 nm. The charge generation layer from bottom to top includes a TPBi layer with a thickness of 30 nm, a MoO3 layer with a thickness of 3 nm, and an NPB layer with a thickness of 20 nm. The blue light organic light emission layer is an mCP:FIrpic layer with a thickness of 20 nm. The electron transport layer is a TPBi layer with a thickness of 35 nm. The electron injection layer is a LiF layer with a thickness of 1 nm. The cathode is an Al layer with a thickness of 120 nm.

[0081] This embodiment also provides a method for fabricating the above-mentioned device, including the following steps:

[0082] (1) Preparation of the anode: Same as in Example 3;

[0083] (2) Preparation of composite hole transport layer: Same as in Example 3;

[0084] (3) Preparation of red-light quasi-two-dimensional perovskite emitting layer by vacuum evaporation: The device obtained in step (2) is transferred to the vacuum evaporation chamber and the vacuum degree is evaporated to 1×10 -4 Pa; PbI2, PEAI, and CsBr were co-deposited in three separate evaporation boats, with the evaporation rates of PbI2, PEAI, and CsBr controlled at 0.32 Å / s, PEAI at 0.17 Å / s, and CsBr at 0.22 Å / s, respectively, to a co-deposition thickness of 65 nm. The device temperature was maintained at 45 °C. After deposition, the device was annealed in situ at 105 °C for 25 min in a vacuum chamber.

[0085] (4) Preparation of perovskite quantum dot modification layer: The CsPbCl3 perovskite quantum dot dispersion synthesized in Example 1 was spin-coated onto the surface of the red perovskite luminescent layer at a speed of 3000 rpm for 40 s. Then, it was annealed on a hot plate at 75℃ for 7 min to form a CsPbCl3 perovskite quantum dot modification layer with a thickness of about 4 nm.

[0086] (5) Preparation of the charge generation layer: Same as in Example 3;

[0087] (6) Preparation of blue organic light-emitting layer: basically the same as in Example 3, except that the doping concentration of Firpic is 15wt% and the co-deposition thickness is 20 nm.

[0088] (7) Preparation of electron transport layer, electron injection layer and cathode: Same as in Example 3.

[0089] Example 5

[0090] This embodiment provides a vacuum-deposited perovskite-organic hybrid stacked white LED, which, from bottom to top, includes: an anode, a composite hole transport layer, a red quasi-two-dimensional perovskite light-emitting layer, a perovskite quantum dot modification layer, a charge generation layer, a blue organic light-emitting layer, an electron transport layer, an electron injection layer, and a cathode.

[0091] The anode is ITO glass, and the composite hole transport layer, from bottom to top, consists of a 30 nm thick PEDOT:PSS layer, a 15 nm thick PTAA layer, and a 20 nm thick PVK layer. The red quasi-two-dimensional perovskite emitting layer is a 62 nm thick PEA2CsPb2(I) layer prepared by vacuum evaporation. 0.7 Br 0.3 7. The perovskite quantum dot modification layer is a CsPbCl3 perovskite quantum dot layer with a thickness of 3 nm. The charge generation layer from bottom to top includes a TPBi layer with a thickness of 30 nm, a MoO3 layer with a thickness of 6 nm, and an NPB layer with a thickness of 30 nm. The blue light organic light emission layer is an mCP:FIrpic layer with a thickness of 18 nm. The electron transport layer is a TPBi layer with a thickness of 32 nm. The electron injection layer is a LiF layer with a thickness of 1 nm. The cathode is an Al layer with a thickness of 120 nm.

[0092] This embodiment also provides a method for fabricating the above-mentioned device, including the following steps:

[0093] (1) Preparation of the anode: Same as in Example 3;

[0094] (2) Preparation of composite hole transport layer: Same as in Example 3;

[0095] (3) Preparation of red-light quasi-two-dimensional perovskite emitting layer by vacuum evaporation: The device obtained in step (2) is transferred to the vacuum evaporation chamber and the vacuum degree is evaporated to 1×10 -4 Pa; PbI2, PEAI, and CsBr were co-deposited in three separate evaporation boats, with the evaporation rates of PbI2, PEAI, and CsBr controlled at 0.3 Å / s, PEAI at 0.16 Å / s, and CsBr at 0.22 Å / s, respectively, to a co-deposition thickness of 62 nm. The device temperature was maintained at 42 °C. After deposition, the device was annealed in situ at 105 °C for 20 min in a vacuum chamber.

[0096] (4) Preparation of perovskite quantum dot modification layer: The CsPbCl3 perovskite quantum dot dispersion synthesized in Example 1 was spin-coated onto the surface of the red perovskite luminescent layer at a speed of 3000 rpm for 40 s. Then, it was annealed on a hot plate at 70℃ for 7 min to form a CsPbCl3 perovskite quantum dot modification layer with a thickness of about 3 nm.

[0097] (5) Preparation of the charge generation layer: Same as in Example 3;

[0098] (6) Preparation of blue organic light-emitting layer: basically the same as in Example 3, except that the doping concentration of Firpic is 5wt% and the co-deposition thickness is 18 nm.

[0099] (7) Preparation of electron transport layer, electron injection layer and cathode: Same as in Example 3.

[0100] Comparative Example 1

[0101] Comparative Example 1 is basically the same as Example 2, except that step (4) is omitted.

[0102] Comparative Example 2

[0103] Comparative Example 2 is basically the same as Example 3, except that step (4) is omitted.

[0104] Experimental device performance analysis

[0105] Figure 4 The electroluminescence (EL) spectra of the single-junction red perovskite LED devices in Example 2 and Comparative Example 1 (without CsPbCl3 perovskite quantum dot modification layer) are shown below. Figure 4 As shown, the emission peaks of both devices are located at 672 nm, which belong to the emission peak of the red light quasi-two-dimensional perovskite luminescent layer. Furthermore, no other emission peaks that may originate from quantum dots appeared in the EL spectrum of the device in Example 2, proving that the CsPbCl3 perovskite quantum dots did not participate in the electroluminescence process, but only served as a modification layer at the interface.

[0106] Figure 5 The voltage-current density-luminance curves for the single-junction red perovskite LED devices in Example 2 and Comparative Example 1 are shown. From... Figure 5 It can be seen that when the brightness is 1 cd / m 2 In Example 2, the turn-on voltage of the device is 3 V, lower than the 4 V of the device in Comparative Example 1. Furthermore, at drive voltages above 3 V, the current density of the device in Example 2 is significantly greater than that of the device in Comparative Example 1, indicating improved electron injection efficiency. In the low-voltage region (<3 V), the leakage current of the target device is even smaller, due to improved film quality after quantum dot passivation defects. The maximum brightness of the device in Example 2 is 3887 cd / m². 2 This is far higher than the 1213 cd / m² of the comparative example 1 device. 2 .

[0107] Figure 6 The images show the EL spectra of the multilayer white LED device in Example 3 at different voltages. Figure 6It can be seen that within the voltage range of 7-13 V, the EL spectrum always exhibits two emission peaks at 472 nm and 672 nm, respectively. Among them, 472 nm is the emission peak of the blue organic light-emitting layer, and 672 nm is the emission peak of the red quasi-two-dimensional perovskite light-emitting layer. The two complement each other to form white light. The intensity of the blue light emission peak in the spectrum continuously increases with the increase of voltage, and the intensity ratio of blue light to red light remains relatively stable within the wide voltage range of 8-12 V, so as to obtain stable white light emission.

[0108] Figure 7 This is a graph showing the CIE color coordinates of the multilayered white LED device in Example 3 as a function of voltage. From... Figure 7 It can be seen that within the 8-13V range, the CIE coordinates are stable at (x=0.323±0.023, y=0.316±0.018), which is very close to the CIE coordinates of standard white light (0.333, 0.333). When the voltage exceeds 12V, the blue light intensity continues to increase while the red light intensity decreases slightly. This is attributed to performance degradation caused by the imbalance of charge carrier injection under high voltage and ion migration in the perovskite, but the white light color coordinates remain within an acceptable range.

[0109] Figure 8 This is the voltage-current density-brightness curve of the multilayer white LED device in Example 3. From... Figure 8 It can be seen that the start-up voltage of this device is 6 V. As the voltage increases, the current density and brightness of the device also increase, with the maximum brightness reaching 5327 cd / m². 2 . Figure 9 This is the current density-external quantum efficiency curve for the stacked white LED in Example 3. From... Figure 9 It can be seen that the highest EQE of this device is 17.1%. Figure 9 The middle illustration is a photograph of the device in operation.

[0110] Figure 10 The EL spectra of the stacked white LED device in Comparative Example 2 (without the CsPbCl3 perovskite quantum dot modification layer) at different operating voltages are shown. Figure 10 It can be seen that under different voltages, the device also exhibits two emission peaks, namely 472 nm (blue light) and 672 nm (red light). Among them, 472 nm is the emission peak of the blue light organic light-emitting layer, and 672 nm is the emission peak of the red light quasi-two-dimensional perovskite light-emitting layer. The two complement each other to form white light. However, in this device, blue light is absolutely dominant, while the red light emission peak is weak. Under this condition, white light emission cannot be achieved. Figure 11 The voltage-current density-brightness curves of the multilayer white LED device in Comparative Example 2 are shown. Figure 11 As shown, the device has a start-up voltage of 7 V and a maximum brightness of 1632 cd / m².2 Compared to the stacked white LED device in Example 3, the performance difference of the stacked white LED device in Comparative Example 2 mainly stems from the severe lack of electron injection in the red perovskite units without CsPbCl3 perovskite quantum dot modification. This results in a significantly lower luminous intensity compared to the blue units, making it impossible to achieve white light balance through color mixing. Furthermore, nonradiative recombination caused by perovskite surface defects further weakens red light emission. Comparative Example 2 fully demonstrates the indispensability of the CsPbCl3 perovskite quantum dot modification layer for achieving efficient white light.

[0111] Although preferred embodiments of the invention have been described, those skilled in the art, upon learning the basic inventive concept, can make other changes and modifications to these embodiments. Therefore, the appended claims are intended to be interpreted as including the preferred embodiments as well as all changes and modifications falling within the scope of the invention.

[0112] Obviously, those skilled in the art can make various modifications and variations to this invention without departing from its spirit and scope. Therefore, if these modifications and variations fall within the scope of the claims of this invention and their equivalents, this invention also intends to include these modifications and variations.

Claims

1. A vacuum-deposited perovskite-organic hybrid multilayer white LED, characterized in that, The device comprises an anode, a composite hole transport layer, a red quasi-two-dimensional perovskite emitting layer, a perovskite quantum dot modification layer, a charge generation layer, a blue organic emitting layer, an electron transport layer, and a cathode, which are stacked sequentially. The perovskite quantum dot modification layer is disposed between the red quasi-two-dimensional perovskite emitting layer and the charge generation layer. The red quasi-two-dimensional perovskite emitting layer is formed by multi-source vacuum evaporation.

2. The vacuum-deposited perovskite-organic hybrid multilayer white LED according to claim 1, characterized in that, The perovskite quantum dot modification layer is CsPbCl3 perovskite quantum dots, with an average particle size of 9.9±0.02 nm and an emission peak at 408 nm.

3. The vacuum-deposited perovskite-organic hybrid multilayer white LED according to claim 1, characterized in that, The red-light quasi-two-dimensional perovskite luminescent layer is formed by multi-source vacuum co-evaporation of lead iodide, phenylethyl ammonium iodide and cesium bromide.

4. The vacuum-deposited perovskite-organic hybrid multilayer white LED according to claim 1, characterized in that, The composite hole transport layer comprises a PEDOT:PSS layer, a PTAA layer, and a PVK layer stacked sequentially.

5. The vacuum-deposited perovskite-organic hybrid multilayer white LED according to claim 1, characterized in that, The charge generation layer comprises a TPBi layer, a MoO3 layer, and an NPB layer stacked sequentially.

6. The vacuum-deposited perovskite-organic hybrid multilayer white LED according to claim 1, characterized in that, The blue light-emitting organic light-emitting layer is an mCP:FIrpic doped layer, wherein the doping concentration of FIrpic is 5-15 wt%.

7. The vacuum-deposited perovskite-organic hybrid multilayer white LED according to claim 1, characterized in that, The thickness of the composite hole transport layer is 55-65 nm, the thickness of the red light quasi-two-dimensional perovskite luminescent layer is 60-65 nm, and the thickness of the perovskite quantum dot modification layer is 3-4 nm.

8. The vacuum-deposited perovskite-organic hybrid multilayer white LED according to claim 1, characterized in that, The thickness of the charge generation layer is 53-66 nm, the thickness of the blue light organic light-emitting layer is 15-20 nm, and the thickness of the electron transport layer is 30-35 nm.

9. The method for preparing a vacuum-deposited perovskite-organic hybrid multilayer white LED according to any one of claims 1-8, characterized in that, Includes the following steps: (1) Patterning etching, cleaning and ultraviolet ozone treatment are performed on the ITO glass substrate, and a composite hole transport layer is prepared on the ITO glass substrate by solution spin coating. (2) A red light quasi-two-dimensional perovskite luminescent layer was prepared on the composite hole transport layer by a multi-source vacuum co-evaporation method; (3) Spin-coating a perovskite quantum dot dispersion onto the red light quasi-two-dimensional perovskite luminescent layer, and then annealing to form a perovskite quantum dot modification layer; (4) A charge generation layer is formed by vacuum evaporation on the perovskite quantum dot modified layer; (5) A blue organic light-emitting layer is formed by vacuum evaporation on the charge generation layer; (6) An electron transport layer and a cathode are sequentially deposited on the blue organic light-emitting layer.

10. The method for preparing a vacuum-deposited perovskite-organic hybrid multilayer white LED according to claim 9, characterized in that, In the multi-source vacuum co-evaporation method described in step (2), the evaporation rate of lead iodide is 0.3-0.32 Å / s, the evaporation rate of phenylethyl ammonium iodide is 0.15-0.17 Å / s, the evaporation rate of cesium bromide is 0.2-0.22 Å / s, the substrate temperature is 40-45℃, the in-situ annealing temperature is 100-105℃, and the annealing time is 20-25 min; in step (3), the annealing temperature is 70-75℃, and the time is 5-7 min.